Students’ perception and preference towards open and distance learning (ODL) during covid-19 pandemic: A case study of studio-based learning / Atikah Fukaihah Amir and Ruwaidah Borhan - Amir, Atikah Fukaihah; Borhan, Ruwaidah (Universiti Teknologi MARA, Perak, 2022)
Open and Distance Learning (ODL) has been widely known to the academic institutions as one of the methods in teaching and learning since COVID-19 pandemic hit nationwide on December 2019. Since then, many educational institutions have started to consider conducting the classes through online platforms such as Google Meet, Cisco WebEx, Microsoft Teams and others. Design-based studio is one of the design stream classes, which practically uses studio classes physically to develop many creative design ideas, skills, innovation, solution, and is considered as the real value of design studio education. However, the studio classes were switched to online platform, and teaching and learning strategy needed to be modified to deal with this issue, dramatically. Thus, the aim of this study is to identify the most effective delivery method in teaching and learning for current best in educational practices. 14 sets of questions in Google Form questionnaire were distributed on week 14 to the students of Landscape Architecture. A total of 261 students responded out of 394 students enrolled in the Landscape Architecture Design studio. The students were in Semester 2, 4 and 6. The students were selected based on the large number of student’s enrollment. The results showed that the students enjoyed learning using Whatsapp, Google Meet and Google Classroom as a synergistic medium for critic sessions. The research suggests three stages of tutorial sessions to suit the needs of the student’s preference.